Chapter Constructing Territoriality “From Below”: Collective Action, Micropolitics, and Landscape in the Duero Plateau (Tenth–Eleventh centuries) - Martín Viso, Iñaki (Firenze University Press, 2025)
The aim of this article is to analyse patterns of territoriality constructed “from below”, based on evidence drawn from a wide range of territories, which were held together by the presence of local initiatives instead of being linked automatically to the central-authority organisation. As this situation was typical of the Duero Plateau, three case studies have been chosen (Ausín, Valdesaz, and Palenzuela). An analysis of these cases shows that the territories were shaped around collective action and focused on common goals, mutual defence practices, and the selection of complementary riverside and mountain landscapes. These arenas of local micropolitics were integrated into the encompassing powers, breaking with the early medieval idea of “deterritorialisation”.